Synchronized chaotic phase masks for encrypting and decrypting images (2008)
ABSTRACT: This paper presents an alternative to secure exchange of encrypted information through public open channels. Chaotic encryption introduces a security improvement by an efficient masking of the message with a chaotic signal. Message extraction by an authorized end user is done using a synchronization procedure, thus allowing a continuous change of the encrypting and decrypting keys. And optical implementation with a 4f optical encrypting architecture is suggested. Digital simulations, including the effects of missing data, corrupted data and noise addition are shown. These results proof the consistency of the proposal, and demonstrate a practical way to operate with it. Keywords: Optical encryptionChaotic phase generationSynchronization system